The Influence of Competency Development and Performance Evaluation on Teacher Productivity at SMPN 6 Karawang - Rahayu, Indriana; Nandang, Nandang; Yudha Rahman, Shandikha Arya (Economics and Digital Business Review, 2026)
Teachers play a very important role in improving the quality of education, so teacher productivity is a major factor in achieving learning objectives in schools. Teacher productivity is influenced by various elements, one of which is competency development and performance evaluation. The purpose of this study is to examine and analyze the impact of competency development and performance evaluation on teacher productivity at SMPN 6 Karawang Barat. The method used in this study was quantitative verification based on data analyzed using statistics. The population and sample size in this study were 50 teachers selected using saturated sampling technique. Data were collected using a closed questionnaire, and data analysis was performed using multiple linear regression. The results of the study indicate that competency development and performance evaluation have a significant positive impact on teacher productivity, both separately and together. The coefficient of determination (R²) value of 0.853 shows that 85.3% of the change in teacher productivity can be explained by these two variables, while the remaining percentage is influenced by other factors outside the scope of the study.